Adverse drug reactions in children: reports to the UK yellow card scheme 2000–2009. (4th April 2011) - Hawcutt, D B; Mainie, P; Appleton, R; Smyth, R; Pirmohamed, M
Abstract : Aims: Rational use of medicines in children requires knowledge of both the efficacy and adverse drug reaction (ADR) profile of individual drugs. The Medicines and Healthcare Regulatory Authority (MHRA) in the UK runs a national spontaneous reporting system (Yellow Card Scheme) to collect 'suspected' ADRs for all medicines. To increase the data for paediatric medicines, current MHRA advice is to report all suspected ADRs in paediatric patients. Yellow Cards submitted in the UK between 2000 and 2009 were analysed. Methods: Data on all UK spontaneous 'suspected' ADRs reported to the MHRA in patients ≤16 years from the years 2000–2009 were supplied in 2 datasets, inclusive and exclusive of vaccine related ADRs. Data, when provided on the Yellow Card by the reporter, included age, type of reaction, medication and type of reporter, but were unlinked. Medications were divided into therapeutic classes to aid specialists to determine rates of reporting in their area. Results: From 2000to 2009, 222 755 Yellow Card reports were received by the MHRA, 31 726 (14.2%) were for children and young people <16 years, an average of over 8 reports per day. Vaccines were included on 22 102 (69.7%) of paediatric ADR reports, with Neisseria meningidis vaccine reported most frequently (12 106 reports) as a result of the Meningitis C vaccination campaign in 2000. Excluding vaccines, the medications most commonly reported were methylphenidate (653 reports) and atomoxetine (491). The commonest symptom reported in the total paediatric dataset was headache (3163 reports); non-vaccine dataset was vomiting (374). Reporting by doctors decreased over time (45.7% of all paediatric reports in 2001, 27.1% 2009). Nurse and patient reporting were introduced in this time (2002 and 2005 respectively). Nurse reporting increased (19.6% 2002, 41.8% 2009). The percentage of reports from patients/parents/carers more than doubled but remain an infrequent source of reports (1.5% 2005, 4.0% 2009). Conclusions: Reporting of ADRs is variable depending on the medication or therapeutic class, and overall underreporting is probably common. All suspected paediatric ADRs should continue to be reported to improve and optimise the evidence for the rational use of medicines in children.